Atg7 Induces Basal Autophagy and Rescues Autophagic Deficiency in CryAB R120G Cardiomyocytes - J. Scott Pattison; Hanna Osińska; Jeffrey Robbins (2011)
Rationale: Increasing evidence suggests that misfolded proteins and intracellular aggregates contribute to cardiac disease and heart failure. Several cardiomyopathies, including the αB-crystallin R120G mutation (CryAB R120G ) model of desmin-related cardiomyopathy, accumulate cytotoxic misfolded proteins in the form of preamyloid oligomers and aggresomes. Impaired autophagic function is a potential cause of misfolded protein accumulations, cytoplasmic aggregate loads, and cardiac disease. Atg7, a mediator of autophagosomal biogenesis, is a putative regulator of autophagic function. Objective: To determine whether autophagic induction by Atg7 is sufficient to reduce misfolded protein and aggregate content in protein misfolding-stressed cardiomyocytes. Methods and Results: To define the gain and loss of function effects of Atg7 expression on CryAB R120G protein misfolding and aggregates, neonatal rat cardiomyocytes were infected with adenoviruses expressing either wild-type CryAB or CryAB R120G and coinfected with Atg7 adenovirus or with Atg7 silencing siRNAs to produce gain-of or loss-of Atg7 function. Atg7 overexpression effectively induced basal autophagy with no detrimental effects on cell survival, suggesting that Atg7 can activate autophagy with no apparent cytotoxic effects. Autophagic flux assays on CryAB R120G -expressing cardiomyocytes revealed reduced autophagic function, which probably contributed to the failure of misfolded proteins and aggregates to be cleared. Coexpression of Atg7 and CryAB R120G significantly reduced preamyloid oligomer staining, aggregate content, and cardiomyocyte cytotoxicity. Conversely, Atg7 silencing in the CryAB R120G background significantly inhibited the already reduced rate of autophagy and increased CryAB R120G aggregate content and cytotoxicity. Conclusions: Atg7 induces basal autophagy, rescues the CryAB R120G autophagic deficiency, and attenuates the accumulation of misfolded proteins and aggregates in cardiomyocytes.